Literasi Kesehatan: Pemberdayaan Sekaa Teruna Teruni dalam Penanganan Kegawatdaruratan Pre-Hospital - Agustini, Ni Luh Putu Inca Buntari; Wahyunadi, Ni Made Dewi; Yusniawati, Yustina Ni Putu; Sanjana, I Wayan Edi; Dewi, Ni Putu Ayu Ratna; Putra, Komang Ardidhana Nugraha; Wijayantha, I Putu Arya; Wardana, Dewa Gede Wisnu (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2024)
Background: Lay people are the first and main helpers for victims who experience emergencies outside the hospital. However, facts on the ground show that people are often confused about providing assistance to victims at the scene and tend to wait for the medical team, thereby missing the "golden time" of first aid to victims outside the hospital. One of the efforts that must be made to overcome this is to improve the behavior of ordinary people in carrying out BT&CLS skills. Counseling and simulations about BT&CLS are an important solution and effort to improve the behavior of ordinary people in providing prehospital emergency assistance. Purpose: The aim of this community service activity is to improve the behavior of ordinary people by empowering Sekaa Teruna Teruni related to BT&CLS skills through counseling and simulation. Method: This stage of PKM activities uses the POAC concept approach, namely planning by conducting assessments with partners about PKM activities, organizing through approaches with related parties, and analyzing the readiness of DM patients to receive training. Actuating and controlling training for Teruni youth students regarding BT&CLS for victims of trauma and cardiac arrest, evaluation, and reflection. Results: The average pre-test result of Sekaa Teruna Teruni before counseling and BT&CLS simulation for trauma and cardiac arrest victims was 52.53, which increased in post-test results to 77.20 after being given training. Conclusion: There was an influence of BT&CLS counseling and simulation on sekaa teruna teruni in the Pedungan Region.